Antibacterial and antibiofilm activities of marine polysaccharide laminarin formulated gold nanoparticles: An ecotoxicity and cytotoxicity assessment. Issue 4 (August 2021) - Vijayakumar, Sekar; Chen, Jingdi; Kalaiselvi, Viswanathan; Divya, Mani; González-Sánchez, Zaira I.; Durán-Lara, Esteban F.; Vaseeharan, Baskaralingam
Abstract: In recent years the use of gold nanoparticles (AuNPs) has risen in fields as different as biomedicine or electronics. The most widely used method for their synthesis is citrate reduction, but alternative green methods are being sought. In this sense, the substitution of citrate with natural compounds such as marine polysaccharides is a noteworthy option. In the present study, laminarin formulated AuNPs (Lm-AuNPs) were synthesized, and their antibacterial and antibiofilm activities, toxicity, and ecotoxicity were evaluated. First, the physicochemical features of the green synthesized Lm-AuNPs were thoroughly evaluated. Lm-AuNPs were highly crystalline, had a spherical shape and a mean particle size of 10–80 nm. The photocatalytic activity of Lm-AuNPs was assessed by the degradation of Methylene Blue (MB), revealing a high decomposition from 60 min. The in vitro antibacterial activity of Lm-AuNPs against the aquatic fish pathogen Aeromonas hydrophila was confirmed by the inhibition of bacterial growth. Furthermore, the antibiofilm activity against A. hydrophila was evaluated, detecting the biofilm growth inhibition at 100 μg/ml of Lm-AuNPs. The in vivo antibacterial activity evaluation was carried out by treating Artemia salina infected by A. hydrophila with Lm-AuNPs, which decreased the mortality rate. Moreover, the cytotoxicity evaluation indicated that Lm-AuNPs did not affect Vero cells' viability up to 100 μg/ml. Likewise, the ecotoxicity assessment of Lm-AuNPs on fresh and marine water microcrustaceans Daphnia similis and Artemia salina showed no significant mortality up to 400 μg/ml. Graphical Abstract: ga1 Highlights: Marine polysaccharide laminarin was used for the biogenic synthesis of gold nanoparticles. Lm-AuNPs exhibited a good photocatalytic activity. Lm- AuNPs effectively repressed the biofilm formation of A. hydrophila at 100 μg/ml. Lm-AuNPs shown no cytotoxicity on Vero cells up to 100 μg/ml. Lm-AuNPs did not affect the Artemia salina and Daphnia similis survival.